2017
DOI: 10.1161/jaha.117.005948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chamber Dilatation on the Prognostic Value of Left Ventricular Geometry in Hypertension

Abstract: BackgroundThe different geometric patterns of the left ventricle may or may not coexist with chamber dilatation. The prognostic impact of such a combination is unclear.Methods and ResultsWe studied a cohort of 2635 initially untreated patients with hypertension, mean age 50 years. At entry, 24‐hour ambulatory blood pressure progressively increased across the patterns of normal geometry, concentric left ventricular (LV) remodeling, eccentric nondilated LV hypertrophy (LVH), eccentric dilated LVH, concentric non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Whether abnormal LV geometric patterns (i.e. LV concentric remodelling, eccentric and concentric LVH) provide independent prognostic information beyond that conveyed by LVM remains uncertain [7]. It has been shown that these patterns differ from each other in terms of clinical features, comorbidities, hemodynamic profile, LV myocardial function, plasma volume and cardiovascular outcomes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Whether abnormal LV geometric patterns (i.e. LV concentric remodelling, eccentric and concentric LVH) provide independent prognostic information beyond that conveyed by LVM remains uncertain [7]. It has been shown that these patterns differ from each other in terms of clinical features, comorbidities, hemodynamic profile, LV myocardial function, plasma volume and cardiovascular outcomes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 18 In an initially untreated large sample of subjects with hypertension, those with LV dilation, regardless of the hypertrophy pattern, experienced a worse prognosis compared with subjects without LV dilation. 19 20 The authors of the Dallas study suggested to subdivide eccentric and concentric LVH into two subgroups based on the presence or absence of LV dilation. 16 In this study, subjects with LV dilation were at higher risk of cardiovascular death and heart failure compared with those without LV dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Than 2 groups were also formed: the first one was the hypertrophic type -eccentric and concentric hypertrophy, indicating an unfavorable, and the second one was non-hypertrophic type with normal geometry and concentric remodeling that was regarded as favorable. Such a categorization was done in accordance with contemporary international data [6][7][8].…”
Section: Methodsmentioning
confidence: 99%